Representasi Motivasi Intrinsik Perkembangan Karier pada Karakter Rara dalam “Film Imperfect” - Ferdian, Fina Ayu; Amaliyah, Amaliyah; Sinulingga, Rizky Amalia; Dimisyqiyani, Erindah; Aji, Gagas Gayuh (Journal of Educational Research and Humaniora (JERH), 2025)
Intrinsic motivation plays an important role in encouraging individuals to grow both personally and professionally in order to achieve their desired careers. This study aims to explore the representation of intrinsic motivation as portrayed by the character Rara in the film 'Imperfect' in the process of career development and audience perception. Using a descriptive qualitative method, this research provides in-depth observations on how intrinsic motivation plays a crucial role in the formation of professional identity, resilience in facing external pressure, and success in developing an authentic career. The character Rara is depicted as an individual whose physical appearance does not meet beauty standards, who constantly faces discrimination, and struggles with low self-esteem. Rara's intrinsic motivation is evident in her career development, where the drive to change and improve her quality comes from internal needs. Her decision to change her appearance to attain a managerial position is based on a personal desire to prove her abilities and gain recognition for her competence as well as achieve self-growth. Intrinsic motivation can clash with workplace norms when personal values conflict with organizational expectations. Through the film, viewers are introduced to the importance of intrinsic motivation in shaping an authentic career journey and social criticism regarding beauty standards. This research shows that the role of visual media, such as film, plays a crucial role in shaping society's understanding of intrinsic motivation, providing an opportunity to educate viewers about the importance of intrinsic motivation in career development.